Prevention of Hypotension following Spinal Anaesthesia in Caesarean Section - then and now - Mitra, J K (Kathmandu University Medical Journal, 2012)
Hypotension during spinal anaesthesia for caesarean section remains a common scenario in our clinical practice. Certain risk factors play a role in altering the incidence of hypotension. Aortocaval compression counteraction does not help to prevent hypotension. Intravenous crystalloid prehydration has poor efficacy; thus, the focus has changed toward co-hydration and use of colloids. Phenylephrine is established as a first- line vasopressor, although there are limited data from high-risk patients. Ephedrine crosses the placenta more than phenylephrine and cause possible alterations in the foetal physiology. http://dx.doi.org/10.3126/kumj.v8i4.6242 Kathmandu Univ Med J 2010;8(4):415-19